Synthesis of cadmium selenide thin films at low-temperature by simple chemical route and their characterization - Hankare, P. P.; Delekar, S. D.; Asabe, M. R.; Chate, P. A.; Bhuse, V. M.; Khomane, A. S.; Garadkar, K. M.; Sarwade, B. D. (Journal of Physics and Chemistry of Solids, 2006)
Crystalline CdSe thin film has been deposited using appropriate precursor solution containing cadmium sulfate octahydrate, tartaric acid, potassium hydroxide, ammonia and sodium selenosulfate. The effect of parameters such as bath composition, deposition temperature, pH of the solution, speed of the rotation and the specificity of complexing agent on growth process is studied. The `as-deposited' CdSe thin film was found to be red in color, specularly reflective and well adherent to the glass substrate. The crystalline phase of the deposited sample was hexagonal wurtzite-type. The analysis of optical absorption data shows energy band gap energy (E-g) 2.01 eV. The morphological study and compositional analysis of film sample have been discussed. The electrical resistivity of CdSe thin film was found to the order of 10(6) Omega cm. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: XRD

Synthesis, characterization of chemically deposited indium selenide thin films at room temperature - Asabe, M. R.; Chate, P. A.; Delekar, S. D.; Garadkar, K. M.; Mulla, Imtiaz S.; Hankare, P. P. (Journal of Physics and Chemistry of Solids, 2008)
Polycrystalline In2Se3 semiconducting thin films were prepared by using relatively simple chemical bath deposition method at room temperature by the reaction between indium chloride, tartaric acid, hydrazine hydrate and sodium selenosulphate in an aqueous alkaline medium. Various preparative conditions of thin film deposition are outlined. The as grown films were found to be transparent, uniform, well adherent and red in color. The films were characterized using X-ray diffraction (XRD), scanning electron microscopy, atomic absorption spectroscopy and energy dispersive atomic X-ray diffraction (EDAX). The XRD analysis of the film showed the presence of polycrystalline nature with hexagonal crystal structure. SEM study revels that the grains are homogenous, without cracks or pinholes and well covers the glass substrate. The optical absorption and electrical conductivity was measured. The direct optical band gap value for the films was found to be of the order of 2.35eV at room temperature and have specific electrical conductivity of the order of 10(-2) (Omega cm)(-1) showing n-type conduction mechanism. The utility of the adapted technique is discussed from the view-point of applications considering the optoelectric and structural data. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Semiconductor

Synthesis and characterization of CoCrxFe2-xO4 nanoparticles - Hankare, P. P.; Sankpal, U. B.; Patil, R. P.; Mulla, Imtiaz S.; Lokhande, P. D.; Gajbhiye, N. S. (Journal of Alloys and Compounds, 2009)
Spinel-phase nanocrystalline CoCrxFe2-xO4 powders (0.0 <= x <= 2.0) were synthesized by citrate-gel precursor method. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM). transmission electron microscopy (TEM) and infra-red spectroscopy (FT-IR). The XRD and selected-area electron diffraction (SAED) patterns indicated that the synthesized nanoparticles have single-phase spinet structure without the presence of any other impurities. The changes in electrical and magnetic properties of different stiochiometric compositions have also been investigated. It is seen that with increase in chromium contents, the measured magnetic hysteresis loops become narrow with decreasing trend in saturation magnetization. Electrical resistivity indicated that all the compounds are semiconducting nature. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Magnetic measurements; Sintering; transmission electron microscopy; X-ray diffraction

Synthesis, characterization and effect of sintering temperature on magnetic properties of MgNi ferrite prepared by co-precipitation method - Hankare, P. P.; Jadhav, S. D.; Sankpal, U. B.; Chavan, Santosh S.; Waghmare, K. J.; Chougule, B. K. (Journal of Alloys and Compounds, 2009)
Mixed MgNi ferrites with composition Mg(0.5)Ni(0.5)Fe(2)O(4) where the mole fraction for Ni (x = 0, 0.25, 0.75, 0.5 and 1) were prepared by following co-precipitation method at temperature 110 degrees C and maintaining a pH of solution equal to 9.5 enable to achieve large particle surface area. The resultant materials obtained in powder form were sintered at different temperatures. Thermogravimetry (TGA), X-ray diffraction (XRD) and scanning electron microscopy, technique were applied to obtain structural parameters. The XRD patterns reveal the presence of(311) peak as the most intense one. The intensity of XRD peak increases with increase in sintering temperature. The saturation magnetization values showed increasing trend with increase in sintering temperature from 2.37 to 29.76 emu/g. These results along with the analysis of SEM micrographs are interpreted in terms of increase in particle grain size with increase in sintering temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Ferrites; FT-IR; scanning electron microscopy; X-ray diffraction

Synthesis and characterization of nanocrystalline zinc substituted nickel ferrites - Hankare, P. P.; Sankpal, U. B.; Patil, R. P.; Mulla, Imtiaz S.; Sasikala, R.; Tripathi, A. K.; Garadkar, K. M. (Journal of Alloys and Compounds, 2010)
Nanocrystalline zinc substituted nickel ferrites, Ni(1-x)Zn(x)Fe(2)O(4) (0.0 <= x <= 1.0) have been prepared by citrate gel auto-combustion method. The effect of zinc ion content on structural, electrical transport and magnetic properties has been studied. The X-ray diffraction (XRD) pattern revealed that, all the compositions possess single-phase spinel structure. The nano-sized grain structure formation was confirmed by transmission electron microscopy (TEM). The dc electrical resistivity shows the samples are semiconducting in nature. The magnetic measurements showed that the composition Ni(0.6)Zn(0.4)Fe(2)O(4) has maximum saturation magnetization (M(s)) while high coersivity (Hc) for ZnFe(2)O(4). Thermoelectric power measurement study showed that the compounds, with x <= 0.4 are p-type and for x > 0.4 behaves n-type conduction mechanism. (C) 2010 Published by Elsevier B.V.
Keywords: Electron microscopy; Magnetic; Sintering; X-ray diffraction

Synthesis and characterization of nickel selenide thin films deposited by chemical method - Hankare, P. P.; Jadhav, B. V.; Garadkar, K. M.; Chate, P. A.; Mulla, Imtiaz S.; Delekar, S. D. (Journal of Alloys and Compounds, 2010)
Nickel selenide thin films have been deposited using chemical bath method on non-conducting glass substrates in a tartarate bath containing nickel sulphate octahydrate, hydrazine hydrate, sodium seleno-sulphate in an aqueous alkaline medium. The grown films were uniform, well adherent and black in color. The films were characterized using X-ray diffraction, scanning electron microscopy, optical absorption and electrical measurements. The nickel selenide thin film revealed polycrystalline nature with hexagonal system. The direct optical band gap of the film was found to be 1.61 eV. Electrical resistivity of film was observed in the order of 10(3) (Omega cm) with p-type conduction mechanism. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Crystal growth; Semiconductors; Thin films; X-ray diffraction

Synthesis and characterization of chemically deposited nickel substituted CdSe thin film - Hankare, P. P.; Jadhav, B. V.; Chate, P. A.; Sathe, D. J.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2011)
The technologically important Cd(0.5)Ni(0.5)Se thin film has been developed by solution growth technique on non-conducting glass substrate in tartarate bath containing Cd(+2), Ni(+2) ions and sodium selenosulphate in an aqueous alkaline medium at room temperature. Various preparative conditions of the thin films are outlined. The films were characterized by X-ray diffraction, scanning electron microscope, optical absorption and electrical measurements. The X-ray diffraction study indicates that the film is polycrystalline in nature with hexagonal phase. Scanning electron micrograph shows that the film is homogeneous with well-defined grains. The films have high optical absorption coefficient. Thermoelectric power measurement shows p-type conduction mechanism. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Crystal growth; Electrical conductivity; thin film

Synthesis and characterization of cobalt substituted zinc ferri-chromites prepared by sol-gel auto-combustion method - Hankare, P. P.; Vader, V. T.; Sankpal, U. B.; Patil, R. P.; Jadhav, A. V.; Mulla, Imtiaz S. (Journal of Materials Science-Materials in Electronics, 2011)
Mixed metal oxides having spinel structure shows interesting structural properties. In the present investigation, cobalt substituted zinc ferri-chromites were prepared by sol-gel auto-combustion method. The completion of solid state reaction and the formation of spinel phase were identified using X-ray diffraction technique. All the compounds exhibit cubic spinel symmetry and lattice constant shows an irregular trend with substitution of Co. Infra-red spectral studies shows an two strong bands, one around 600 cm(-1) which is attributed to the intrinsic vibrations of tetrahedral complexes and the other at 400 cm(-1) is due to octahedral one. The morphology and size of the particles was found out by scanning electron microscopy while the elemental compositions by elemental dispersive X-ray spectroscopy. The various compounds of the present system Zn1-xCoxFeCrO4 were also investigated for their thermal and electronic studies.

Structural and surface morphological properties of chemically deposited Mo0.5W0.5S2 thin film - Patil, A. A.; Hankare, P. P.; Gaikwad, A. B.; Garadkar, K. M. (Journal of Materials Science-Materials in Electronics, 2012)
Preparation of layered type semiconductor Mo0.5W0.5S2- thin films has been successfully done by using chemical bath deposition method. Objective of the studies are related to structural, optical, morphological and electrical properties of the thin films. The preparation method is based on the reaction between tartarate complex of Mo and W with thiourea in an aqueous alkaline medium at 363 K. X-Ray diffraction reveals a polycrystalline film composed of both MoS2 and WS2 phases. The optical study shows that the band gap of the film is 1.6 eV. Electrical conductivity is high which is in the order of 10(-3)-10(-2) (Omega cm)(-1).